Comparative analysis of salah (prayer) in the Hanafi and Syafi’i school - Rosmaily, Dania Qistina Aisy; Hassan, Norsafia; Mohd Fisal, Nur Syafiqah; Mohd Yusoff, Nur Aisyah Atiqah; Ibrahim, Safurah (2024)
In this paper we are required to complete an assignment regarding about comparative analysis of salah (prayer) in the Hanafi and Shafi'i school. First and foremost, Salah (prayer) is the worship that occupies the highest place and if a Muslim is obedient in performing obligatory prayers as many as five times a day, it means that he seems to uphold his religion. This study aims to describe the differences of opinion between the Hanafi and Shafi'i schools of thought regarding prayer. Next, the objective of this study is to focus on the prayer procedures of the Hanafi school and the Shafi'i school. The results of this study are analyzed by using field methods to achieve the objectives of the study. The researcher also refers to scientific materials such as books, articles, journals, and writings related to the topic under study. In conclusion, the researcher hope that this study could be helpful for other people to understand comparative analysis of salah (prayer) in the Hanafi and Shafi'i school.